Tekstfortolkeren – Interview med Quentin Skinner - Thorup, Mikkel; Lassen, Frank Beck (Slagmark - Tidsskrift for idéhistorie, 2018)
This interview explores the biographical and methodical background of the Cambridge approach to the history of ideas, an approach also known as intellectual history that has Quentin Skinner as one of its founding and most prolific representatives. The article takes us back to his early years at school and university, his encounters with Collingwood and Wittgenstein and his way into and understanding of intellectual history. The interview then moves onto methodological issues on intentionality and contextualism and what it means to work as an intellectual historian today.